Intelligent Document Processing: The New Frontier of Automation - Karthik Kapula (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Intelligent Document Processing (IDP) represents a transformative evolution in automation, combining Optical Character Recognition (OCR), machine learning, natural language processing, and business rules to extract, classify, and validate data from complex, unstructured documents. As organizations face increasing volumes of diverse documents and stringent regulatory requirements, IDP offers a scalable and secure solution that transcends traditional Robotic Process Automation (RPA) capabilities. This article explores the technological foundations, practical applications, and benefits of IDP across various industries, highlighting its role in accelerating processes such as invoice handling, customer onboarding, and compliance audits. Additionally, it discusses the challenges of implementation, emerging trends, and the strategic impact of IDP on operational efficiency and digital transformation.